Anti-Saccharomyces cerevisiae IgA antibodies are raised in ankylosing spondylitis and undifferentiated spondyloarthropathy. Issue 5 (1st May 2003) - Hoffman, I E A; Demetter, P; Peeters, M; De Vos, M; Mielants, H; Veys, E M; De Keyser, F
Abstract : Objectives: To investigate whether anti- Saccharomyces cerevisiae antibodies (ASCA), a marker for Crohn's disease (CD), are present in spondyloarthropathies (SpA) and in the subgroups ankylosing spondylitis (AS), undifferentiated SpA (uSpA), and psoriatic arthritis (PsA), in comparison with healthy and inflammatory controls (patients with rheumatoid arthritis (RA)). Methods: ASCA IgA and IgG levels were measured with an enzyme linked immunosorbent assay (ELISA) kit (Medipan, Germany) in 26 patients with CD, 108 patients with SpA (43 patients with AS, 20 patients with uSpA, 45 patients with PsA), 56 patients with RA and 45 healthy controls. Gut biopsy samples were available in 18 AS and 10 patients with uSpA, these samples were screened for the presence of inflammation. Results: Both ASCA IgG and IgA levels were raised in CD compared with healthy controls and patients with RA. ASCA IgA, but not IgG levels, were higher in SpA than in both healthy and RA controls. ASCA IgA levels were raised in AS and uSpA, but not in PsA. No significant differences in ASCA IgA levels were noted between patients with SpA with and without histological gut inflammation. Conclusion: ASCA IgA levels are significantly higher in SpA, and more specifically in AS, than in healthy controls and patients with RA. This is the first serum marker associated with SpA. No correlation between the presence of subclinical bowel inflammation and ASCA IgA levels was noted. However, it remains to be evaluated whether patients with SpA with ASCA have an increased risk of developing CD.